An Active Decoupling Method for 6R Robots Based on Denavit-Hartenberg Parameters - Yin Jie; Xi Wanqiang (Jixie chuandong)
Due to the interpenetrating layout of each shaft for the 6R robot, the movement of one joint could affect the other joints. This mechanical coupling could result in the interference of each joint, and an error between theoretical model and actual model would affect the absolute positioning accuracy of the robot. The motion compensation method obtained the coupling amount by measuring the error between the target value and the actual value and the joint angles are compensated. However, an active decoupling method of 6R robot based on Denavit-Hartenberg (D-H) parameters is provided. Firstly, the coupling of robot joints which is calculated through transmission analysis is added to the joint angle for 6R robot. Then, the D-H parameters with coupling are used in the forward kinematics, and the algebraic solution is used to obtain the inverse kinematics. The feasibility of the model is verified by the simulation of the workspace and kinematics through the Matlab robotic toolbox. At the same time, the simulation based on this method is built to compare with the motion compensation method. The above results prove that this method solves the motion coupling problems stemming from mechanical coupling, reduces the error of the robot end position and improves the robot positioning accuracy. Adding the linear coupling quantity to the joint variables does not significantly increase the calculation amount of kinematics for 6R robot, and the solution process is convenient.